Mapping Conceptual Domains and Bridging Concepts in Technology-Enhanced Mathematics Learning: A Bibliometric Study - Siti Aminah; Yunis Sulistyorini (AlphaMath : Journal of Mathematics Education, 2026)
This study examines the research landscape of recent studies in students’ acceptance in technology-enhanced mathematics learning, an increasingly important issue as digital technologies become more widely integrated into mathematics education. Although research in this area has expanded in recent years, previous studies have often treated technological, pedagogical, and cognitive–psychological factors separately, leading to a fragmented understanding of students’ acceptance. This study aimed to map the development of the field, identify its major conceptual domains, examine the interactions among these domains, and explain their implications for future mathematics education research and practice. A bibliometric design was employed using data from the Scopus database. After a systematic screening process, 883 publications published between 2015 and 2026 were analyzed. Publication trend analysis and keyword co-occurrence mapping were conducted using VOSviewer. From 5,259 extracted keywords, 196 met the minimum occurrence threshold and were included in the final analysis. Findings reveal that publication output grew substantially, from 35 articles in 2015 to a peak of 248 in 2025. Furthermore, three major conceptual domains were examined: technology-enhanced mathematics pedagogy, instructional practices and teacher professional development, and cognitive–psychological aspects of mathematics learning. The analysis also reveals bridging concepts, particularly problem solving, motivation, student engagement, learning, and cognition. The novelty of this study lies in its integrative mapping of these domains and their bridging concepts, contributing to a more holistic understanding of students’ acceptance and informing the design of more meaningful technology-enhanced mathematics learning environments.